Selective Extraction of Lithium from Spent Lithium-Ion Manganese Oxide Battery System through Sulfating Roasting and Water-Leaching - Jeraldiny Becker; Sebastian Will; Bernd Friedrich (Metals, 2023)
Sulfating roasting tests were conducted with different agents to investigate lithium recovery from spent lithium-ion manganese oxide (LMO) batteries. In this study, CaSO4 and CaCO3 were used as reactants, and the optimal temperature, residence time, and molar fraction of CaSO4 in a static reactor were determined. In the experiments, the temperature ranged between 620 and 720 °C, and the holding time was between 10 and 40 min. In addition, the molar fraction of CaSO4 varied between 0 and 100%, with the rest being CaCO3. The water leaching was fixed at an S/L ratio of 1/20 and heated to 60 °C for 1 h. The maximum Li yield achieved was 93.4% at 720 °C, 25 min, and a 0.5 molar fraction of CaSO4, and virtually no Mn was present in the solution. Therefore, high selectivity for Mn—which is the major compound in the LMO black mass—was observed. Regarding statistical evaluation, temperature was the most influential parameter and, to a lesser extent, the molar fraction of CaSO4. The product displayed a sintering effect, suggesting that the pyrolyzed black mass and reactive underwent a solid-solid reaction in the selected temperature range.